ҚАРАҚАЛПАҚСТАНДА ИНКЛЮЗИВ ТӘЛИМДИ РАЎАЖЛАНДЫРЫЎ МӘСЕЛЕЛЕРИ - Ешбаев, А.Ж. (ILIM hám JÁMIYET, 2025)
The article discusses the development of inclusive education in Karakalpakstan. In particular, some problems hindering the development of inclusion in universities and general education schools will be analyzed.